Human Parvovirus B19-Induced Acute Glomerulonephritis: A Case Report. (February 2013) - Shimohata, Homare; Higuchi, Takashi; Ogawa, Yujiro; Fujita, Shogo; Nagai, Miho; Imaizumi, Masahiro; Maruyama, Hiroshi; Hirayama, Kouichi; Kobayashi, Masaki
<x xml:space="preserve">Abstract</x> Human parvovirus B19 (HPV B19) infection is well known as a cause of erythema infectiosum in children. Acute glomerulonephritis due to HPVB19 infection is rarely observed in adults. Here, we present the case of a 45-year-old female who showed acute glomerulonephritis induced by HPVB19 infection with various autoantibodies. She had proteinuria (175 mg/g creatinine) and hematuria (20–29 erythrocytes per high-power field) in a urinalysis, and various autoantibodies such as antinuclear antibodies, proteinase-3-antineutrophil cytoplasmic antibodies (PR3-ANCA), antiglomerular basement membrane (GBM) antibodies, and anticardiolipin antibodies in a blood examination. A renal biopsy showed that endocapillary proliferative glomerulonephritis comprised of mononuclear cell infiltration. By using immunofluorescence microscopy, IgG, IgA, IgM, C3, C4, and C1q deposits were detected mainly in glomerular capillaries. Electron-dense deposits were detected in the subendothelial area and mesangial area by using electron microscopy. All symptoms and abnormal laboratory data were self-improved. Our patient's case may provide a clue to the etiology of ANCA-associated vasculitis or lupus nephritis.